Checklist for the Systemic Treatment of Psoriasis Using Biologics: A Delphi Study. Issue 3 (May 2019) - Fahim, Christine; Kim, Ben Whan; Bourcier, Marc; Glassman, Steven; Gooderham, Melinda; Guenther, Lyn; Gulliver, Wayne; Lynde, Charles; Poulin, Yves; Pratt, Melanie; Shear, Neil; Vender, Ronald; et al.
Background: Despite the complexity of psoriasis treatment using biologic therapy, there does not exist a standardized synoptic reporting form for the initiation of this population. The purpose of this study was to use a modified Delphi approach to develop a standard checklist for the standardized documentation of patients receiving systemic biologic therapy for psoriasis. Methods: A modified Delphi survey was conducted over 3 rounds (February 2017 through January 2018). An expert panel generated a 51-item checklist that was proposed to participants. Items were rated on an anchored 1-7 Likert scale. Consensus was defined apriori as ≥ 70% agreement by respondents. Results: A total of 58, 17, and 18 dermatologists participated in 3 consecutive Delphi rounds, respectively. Only half of the dermatologists surveyed reported using a checklist for the management of psoriasis. The final checklist comprised 19, 5, 6, and 9 items pertaining to patient history; physical exam and history of systemic therapy; vaccinations; and lab investigations and bloodwork, respectively. Conclusions: Given the increasing availability and complexity of biologic agents for psoriasis treatment, there is a need to promote standardized documentation for this population. The Checklist for the Systemic Treatment of Psoriasis presents 38 items that should be considered when initiating patients with psoriasis on biologic therapy.